Twist-controlled resonant tunnelling in graphene/boron nitride/graphene heterostructures - Mishchenko, A.; Tu, J.S.; Cao, Y.; Gorbachev, R.V.; Wallbank, J.R.; Greenaway, M.T.; Morozov, S.V.; Morozov, V.E.; Zhu, M.J.; Wong, S.L.; Withers, F.; Woods, C.R.; et al. (Macmillan Publishers Limited, 2014)
Recent developments in the technology of van der Waals heterostructures made from two-dimensional atomic crystals ave already led to the observation of new physical phenomena, such as the metal-insulator transition and Coulomb drag, and to the realisation of functional devices, such as tunnel diodes, tunnel transistors and photovoltaic sensors. An unprecedented degree of control of the electronic properties is available not only by means of the selection of materials in the stack but also through the additional fine-tuning achievable by adjusting the built-in strain and relative orientation of the component layers. Here we demonstrate how careful alignment of the crystallographic orientation of two graphene electrodes, separated by a layer of hexagonal boron nitride (hBN) in a transistor device, can achieve resonant tunnelling with conservation of electron energy, momentum and, potentially, chirality. We show how the resonance peak and negative differential conductance in the device characteristics induces a tuneable radio-frequency oscillatory current which has potential for future high frequency technology.